2016
DOI: 10.1105/tpc.16.00491
|View full text |Cite
|
Sign up to set email alerts
|

Thylakoid Membrane Architecture in Synechocystis Depends on CurT, a Homolog of the Granal CURVATURE THYLAKOID1 Proteins

Abstract: Photosynthesis occurs in thylakoids, a highly specialized membrane system. In the cyanobacterium sp PCC 6803 (hereafter 6803), the thylakoids are arranged parallel to the plasma membrane and occasionally converge toward it to form biogenesis centers. The initial steps in PSII assembly are thought to take place in these regions, which contain a membrane subcompartment harboring the early assembly factor PratA and are referred to as PratA-defined membranes (PDMs). Loss of CurT, the 6803 homolog of grana-shaping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 74 publications
1
46
2
Order By: Relevance
“…Therefore, it is possible that, if hydrocarbons do alter membrane curvature, then this is augmented and orientated by CurT. In DcurT, the thylakoid membranes were still highly curved, indicating that other factors are involved in inducing membrane curvature (Heinz et al, 2016). Homologs of CurT are present in the majority of sequenced cyanobacterial strains (Supplemental Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is possible that, if hydrocarbons do alter membrane curvature, then this is augmented and orientated by CurT. In DcurT, the thylakoid membranes were still highly curved, indicating that other factors are involved in inducing membrane curvature (Heinz et al, 2016). Homologs of CurT are present in the majority of sequenced cyanobacterial strains (Supplemental Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…A homologous protein in Synechocystis, CurT, has recently been shown to have a similar role in thylakoid membranes (Heinz et al, 2016). Deletion of CurT resulted in a reduction in growth and extreme differences in thylakoid membrane organization, with the thylakoids appearing to cross the cytoplasm and not converging on the "thylakoid centers."…”
Section: Discussionmentioning
confidence: 99%
“…Vipp1/IM30‐enriched regions were found to co‐localize with CURT1, a protein supposably inducing TM curvature (Armbruster et al ., ; Heinz et al ., ). Noteworthy, no evidence of direct IM30‐CURT1 interaction has been found yet (Bryan et al ., ; Heinz et al ., ), implying that co‐localization is caused by the membrane curvature. However, the lipid bilayer of curvature‐stressed membranes might be drastically destabilized, which exhibits the risk of proton leakage (Attard et al ., ).…”
Section: Vipp1/im30: a Crucial Player In Thylakoid Membrane Biogenesismentioning
confidence: 97%
“…In agreement with this observation, in the now presented study, IM30 puncta were preferentially identified at curvature‐stressed regions of the TM (Gutu et al ., ). Vipp1/IM30‐enriched regions were found to co‐localize with CURT1, a protein supposably inducing TM curvature (Armbruster et al ., ; Heinz et al ., ). Noteworthy, no evidence of direct IM30‐CURT1 interaction has been found yet (Bryan et al ., ; Heinz et al ., ), implying that co‐localization is caused by the membrane curvature.…”
Section: Vipp1/im30: a Crucial Player In Thylakoid Membrane Biogenesismentioning
confidence: 99%
See 1 more Smart Citation